2017
DOI: 10.15171/ajmb.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of uric acid, urea, ammonia and creatinine of seminal plasma with semen parameters and fertilization rate of infertile couples

Abstract: Background: Ammonia, urea, uric acid, and creatinine are the major non-protein nitrogenous compounds (NPNs). It is reported that the concentration of NPNs in the seminal plasma of normal and infertile individuals is different and sperm is affected by NPNs. Objectives: The aim of this study was to determine the quantities of ammonia, urea, uric acid, and creatinine in seminal plasma and the correlation of these compounds with the fertilization rate after an intracytoplasmic sperm injection (ICSI). Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
1
5
2
Order By: Relevance
“…On one hand, UA may scavenge hydroxyl radicals. On the other hand, UA converts to U which, according to several studies (Allahkarami et al, 2017;Halo Jr. et al, 2018), may be related to a decreased sperm motility, which is in conflict with our results. The correlation analysis revealed significant (P<0.01) and positive (0.651) correlation between PROG and U.…”
Section: Mean Values Of Sperm Quality Parameterscontrasting
confidence: 99%
“…On one hand, UA may scavenge hydroxyl radicals. On the other hand, UA converts to U which, according to several studies (Allahkarami et al, 2017;Halo Jr. et al, 2018), may be related to a decreased sperm motility, which is in conflict with our results. The correlation analysis revealed significant (P<0.01) and positive (0.651) correlation between PROG and U.…”
Section: Mean Values Of Sperm Quality Parameterscontrasting
confidence: 99%
“…However, we do not know any biologically plausible explanation for the associations of urinary speci c gravity and creatinine with sperm mtDNAcn. A negative association was observed between seminal creatinine concentrations and sperm count in patients with intracytoplasmic sperm injection [52], but it is unknown whether urinary creatinine concentration re ects seminal creatinine concentration, and thus the nding of the previous study [52] does not explain the associations observed in this study.…”
Section: Discussioncontrasting
confidence: 56%
“…Accordingly, in this study, we used creatinine as a tracing metric for urine volume from concurrently measured concentration of creatinine in urine and seminal plasma. Few previous studies have reported measuring creatinine in semen samples [15][16][17] but none measured urine creatinine concurrently to quantify urine content of semen samples. One study of eight men after resection of the bladder base displayed pathological leakage of urine into the ejaculate 17 whereas the present study investigated men with normal bladder base sphincter function.…”
Section: Discussionmentioning
confidence: 99%